Holistic Pedagogues: Integrating Islamic Values Into Lecturers’ Leadership Competence - Oemar, Hirawati; Nurdin, Diding; Orgianus, Yan; Mustamiah, Riyadatul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Lecturer leadership competencies include the abilities, knowledge, and skills needed by a lecturer to be an effective leader in the college environment. The leadership role of lecturers is very important in guiding, inspiring, and leading students and academic teams towards successful academic and moral achievement in college. This study aims to determine and identify the leadership competencies of lecturers based on Islamic values in the context of higher education. The research method used is qualitative research with a literature study approach and Focus Group Discussion (FGD). Through literature study, this research explores various relevant sources to find out and identify and describe Islamic values and qualifications required by lecturers in tertiary institutions, especially Islamic tertiary institutions. Furthermore, FGD was conducted with experts to get a direct view of the leadership competence of lecturers based on Islamic values. The results showed that the leadership competence of lecturers based on Islamic values covers several key aspects, namely: fear of Allah, integrity (siddiq), trustful (amanah), visionary (fathonah), effective communication (tabligh), fair (adl), brave and firmness (Shujaâ€™a wahazim), being an example (uswatun hasanah), leadership based on deliberation (syura), responsibility (mashwuwlia), and accountable (shafaf).Â